DESIGN, OPTIMIZATION AND PERFORMANCE EVALUATION OF A SOLAR HEAT COLLECTOR TROUGH AUTOMATED DATA ACQUIZITION SYSTEM - Ibne Shahid, Nashid; Mobashwer Indaleeb, Mustahseen; Akramul Haque, Dewan (Department of Mechanical Engineering, Military Institute of Science and Technology (MIST), 2012)
From the very beginning of the 21st century, the world is craving towards technological advancement. Every continent, every country is fighting for their survival through technology to make their future predictable and safe. Eventually, with the up rising demand of energy, the span of reserved petroleum started to reduce. Throughout the world, price of the petroleum products started to rise rapidly. At this stage researchers started to think about an alternative option as the source of energy. Thus the concept of solar energy came. At present Solar energy is termed as one of the most effective and reliable Renewable energy sources (RESs). The rapid evolution of renewable energy sources during the last two decades resulted in the installation of many solar power units. The production of electricity from renewable energy technologies is mounting much faster than the electric power supply as a whole. Solar power is among the fastest emergent segments of the renewable energy market. Centralized solar power is produced on large farms and fed into an electrical grid. Globally, gridconnected solar capacity increased an average of 60 percent annually from 2004 to 2009, faster than any other energy source. Today, however, solar power still accounts for less than one-half of one percent of the world’s power output. This solar power can be utilized to conserve energy in various ways. Solar heat collector system is one of it. A good reason to use Solar Heat Collector System(SWHS) instead of conventional energy based systems, is that it offsets those greenhouse gases that would have been generated had the water been heated by electric power or natural gas.
In the name of Allah, most Gracious, most Compassionate. First and foremost, our sincere gratitude to our supervisor Dr. Engr. Md. Alamgir Hossain for the valuable guidance, advice and supervision. His encouragement and support from the initial to the final level enabled us to develop a well understanding of the project. His motivation, direction and inspiration were the backbone of our hardship. We also hereby express our heartiest gratitude to those who extended their helping hand in accomplishing the project and thesis by providing advice, care, attention and technical support. Besides, we would like to thank the faculty members of Department of Mechanical Engineering, Military Institute of Science and Technology for providing us all kinds of support. We are indebted to the authority of Military Institute of Science and Technology for providing us necessary funding and good environment and facilities to complete this project. Finally, we would like to thank everybody who was important to make the successful completion of the project and thesis, as well as express our apology that we could not mention personally one by one.
Keywords: Design, Optimization and Performance Evaluation of a Solar Heat Collector Trough Automated Data Acquisition System